HIGHER INSTITUTION STUDENTS’ CHALLENGES IN WRITING JOURNAL ARTICLES: CHARACTERISTICS AND PROPOSED SOLUTIONS - Sahan, Anselmus; Saridewi, Maria P; Wabang, Rince J; Adrianus, Nabung (English Review: Journal of English Education, 2024)
This qualitative study aimed to identify the challenges faced by final semester students in Indonesian tertiary institutions when writing journal articles, and propose potential solutions to these challenges. The study analyzed 32 articles published in Timor University e-journals, selected purposively from 16 study programs. Results showed that the majority of articles (59%) scored 75, indicating a need for improvement. The most significant challenges faced by students were related to introduction and method (13%), results (13%), and discussion (13%). These findings were consistent with the results of a questionnaire analysis, which identified method and abstract (22%), discussion (30%), and all parts (26%) as problematic areas for students. To address these issues, the study proposes a formal mandate requiring all lecturers to accompany their students in writing journal articles. This mandate would provide students with necessary support and guidance to improve their writing skills and meet the acceptable journal template requirements. The proposed solutions aim to alleviate the academic burden faced by thesis advisors, editors, and reviewers, while also improving the quality of articles produced by students.